Mosquito Saliva Modulates Japanese Encephalitis Virus Infection in Domestic Pigs - Park, So Lee; Huang, Yan-Jang S.; Lyons, Amy C.; Ayers, Victoria B.; Hettenbach, Susan M.; McVey, D. Scott; Noronha, Leela E.; Burton, Kenneth R.; Hsu, Wei-Wen; Higgs, Stephen; Vanlandingham, Dana L. (Frontiers in Virology, 2021)
Japanese encephalitis virus (JEV) is a mosquito-borne flavivirus that is the leading cause of pediatric viral encephalitis in Asia. JEV is transmitted by Culex species mosquitoes that also vector several zoonotic flaviviruses. Despite the knowledge that mosquito saliva contains molecules that may alter flavivirus pathogenesis, whether or not the deposition of viruses by infected mosquitoes has an impact on the kinetics and severity of JEV infection has not been thoroughly examined, especially in mammalian species involved in the enzootic transmission. Most JEV pathogenesis models were established using needle inoculation. Mouse models for West Nile and dengue viruses have shown that mosquito saliva can potentiate flavivirus infections and exacerbate disease symptoms. In this study, we determined the impact of mosquito salivary components on the pathogenesis of JEV in pigs, a species directly involved in its transmission cycle as an amplifying host. Interestingly, co-injection of JEV and salivary gland extract collected from Culex quinquefasciatus produced milder febrile illness and shortened duration of nasal shedding but had no demonstrable impact on viremia and neuroinvasion. Our findings highlight that mosquito salivary components can differentially modulate the outcomes of flavivirus infections in amplifying hosts and in mouse models.